Earls Barton Church Tower
Christianity came to England with the Romans, and had been adopted by the Saxons even before St. Augustine's mission from Rome in 597 C.E. It renewed contacts that had lapsed form three hundred years. Saxon Churches were liable to attack from Viking raiders, and often protected themselves by the addition of a tower to act as stronghold and as vantage point. Few of these towers now remain, but this example, which is well inland, is typical. The church building is of a later date.